Law Enforcement of Traffic Violations in Sidoarjo Regency: Penegakan Hukum Pelanggaran Lalu Lintas di Kabupaten Sidoarjo - Syaifullah, Achmad Firman; Rosnawati , Emy (Indonesian Journal of Law and Economics Review, 2025)
General Background: Traffic violations remain a persistent issue in urban areas of Indonesia, reflecting both human behavior and the challenges of law enforcement. Specific Background: In Sidoarjo Regency, the rise in traffic violations and accidents highlights weaknesses in the current legal enforcement system and public awareness. Knowledge Gap: Previous studies have focused mainly on the regulatory framework without assessing the practical alignment between legal procedures and societal needs. Aims: This study analyzes the legal enforcement of minor traffic offenses in Sidoarjo, evaluating public compliance, enforcement consistency, and institutional cooperation under Law Number 22 of 2009. Results: The findings indicate that the effectiveness of law enforcement depends on the availability of resources, public legal awareness, inter-agency collaboration, and adaptive procedures that align with local realities. Novelty: Unlike earlier research, this study integrates juridical-sociological analysis with empirical field data to examine adaptive enforcement mechanisms at the local level. Implications: The research underscores the need for continuous policy innovation, improved coordination among legal institutions, and community-based education to strengthen traffic law compliance. <article class="text-token-text-primary w-full focus:outline-none [--shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(--shadow-height) has-data-writing-block:pt-(--shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto [content-visibility:auto] supports-[content-visibility:auto]:[contain-intrinsic-size:auto_100lvh] scroll-mt-[calc(var(--header-height)+min(200px,max(70px,20svh)))]" dir="auto" tabindex="-1" data-turn-id="request-WEB:4c662ff0-60bf-4584-be01-87094bf6d166-14" data-testid="conversation-turn-4" data-scroll-anchor="false" data-turn="assistant"> <div class="[--thread-content-max-width:40rem] thread-lg:[--thread-content-max-width:48rem] mx-auto max-w-(--thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn" tabindex="-1"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal [.text-message+&]:mt-1" dir="auto" data-message-author-role="assistant" data-message-id="000b9ba8-5037-4d1e-94f6-b1fd01c961b4" data-message-model-slug="gpt-5"> Highlights: Identifies core factors affecting traffic law enforcement in Sidoarjo. Integrates juridical-sociological and empirical approaches. Emphasizes adaptive, community-oriented legal strategies. Keywords: Law Enforcement, Traffic Violations, Legal Awareness, Sidoarjo, Public Policy